PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL DENGAN DIMEDIASIOLEH PEMBERDAYAAN PSIKOLOGIS - Muhamad Ali Sukrajap (LPPM Universitas Proklamasi 45, 2016)
Eighty five employees of a private hospital participated in this study. They are recruited randomly from a finite population (545 employees). Objective of this study is to verify the strength of psychological empowerment as the mediator variable between independent variable (transformational leadership) and two dependent variables (job satisfaction and organizational commitment). There are also four instruments 1). The Minnesota Satisfaction Questionnaire short form (MSQ-short Form), validity ranged from .470-.808, the Cronbach Alpha for reliability coefficient was .912. 2). Organizational Commitment Scale, validity ranged from .370-.851, the Cronbach Alpha for reliability coefficient was .829. 3). The Transformational Leadership Scale, validity ranged from .429-.856, the Cronbach Alpha for reliability coefficient was .966. 4). The Psychological Empowerment Scale, validity ranged from .553-.819, the Cronbach Alpha for reliability coefficient was .914. The hypothesis is that there is a mediation relationship between transformational leadership and job satisfaction and also organizational commitment. This study revealed that the mediator variable is quite strong for the job satisfaction variable. However, the mediator variable is less likely strong for the organizational commitment. It may there were other variables which also influence the dependent variable. Those other variables, however, were not in this research.